Juvenile delinquency and justice in the United States - Johnson, Lee Michael (Carolina Academic Press, 2020)
Introduction : what is delinquency? -- Extent of delinquency : how bad is it? -- "Causes" of delinquency : characteristics of individuals and their environments -- "Causes" of delinquency : social processes -- "Causes" of delinquency : life course processes -- Informal social control -- A brief history of juvenile justice in the United States -- Policing juveniles -- Juvenile court -- Juvenile corrections -- Juvenile justice reform : a human rights perspective -- Current issues in juvenile justice.